Temperature-Driven Divergence in Microbial Consortia and Physicochemical Functionality: A Comparative Study of High- and Medium-Temperature Daqu - Huawei Yuan; Jia Zheng; Liping Ding; Hong Wang; Qin Jiang; Chao Zhang; Tingna Xie; Guohui Nan; Li Li; Kai Lou (Microorganisms)
Daqu, a crucial fermentation starter for Chinese Baijiu, develops distinct microbial and physicochemical profiles depending on fermentation temperature, which significantly influence enzymatic activity and flavor formation. While high-temperature (HT-Daqu, 65 °C) and medium-temperature (MT-Daqu, 60 °C) variants are known to produce different liquor aromas, systematic comparisons of their microbial and physicochemical dynamics remain limited. This study integrated physicochemical assays (moisture, starch, acidity, enzymatic activity) with 16S rRNA and ITS (Internal Transcribed Spacer) sequencing to analyze HT-Daqu (HQ1–HQ3) and MT-Daqu (MQ1–MQ3) from Sichuan breweries. Results revealed that HT-Daqu exhibited significantly lower moisture (p < 0.05) and starch content (p < 0.05) but higher acidity (p < 0.05) compared to MT-Daqu. Enzymatic activities were generally reduced in HT-Daqu, except for neutral protease. Microbial profiling revealed distinct microbial dynamics between HT-Daqu and MT-Daqu: HT-Daqu harbored thermophilic Bacillus (40–60% relative abundance) with reduced fungal diversity, while MT-Daqu prioritized fungal consortia—Aspergillus dominated MQ1 (78%) and Saccharomyces transiently peaked in MQ2 (35%)—which correlated with enhanced saccharification enzyme activities and esterification potential. Alpha-diversity indices confirmed higher bacterial diversity in HT-Daqu and greater fungal richness in MT-Daqu. Correlation networks highlighted temperature-driven linkages, such as Bacillus positively associating with acidity. These findings elucidate the trade-offs between microbial stress adaptation and metabolic efficiency under different thermal regimes, providing actionable insights for optimizing Daqu production through targeted microbial management and temperature control to enhance liquor quality.